Depression Paradox in Cardiovascular Outcomes of Adult Patients with Obstructive Sleep Apnea: Insights from 2 Million Nationwide Hospitalizations - Rupak Desai; Sashwath Srikanth; Shaylika Chauhan; Zainab Gandhi; Warda Shahnawaz; Aleen Rahman; Bisharah Rizvi; Akhil Jain (Thoracic Research and Practice)
OBJECTIVE: Depression is a frequent comorbidity in obstructive sleep apnea (OSA) patients. There is a scarcity of data on the impact of depression on the outcomes of OSA. MATERIAL AND METHODS: Using the National Inpatient Sample (2018), we identified hospitalizations in the US with OSA. Following propensity-score matching, the two cohorts of OSA with depression (OSA+D+) vs. without depression (OSA+D-) were compared for demographic and comorbidities profiles differences. Multivariable regression analyses were performed to assess the odds of events with depression versus those without. RESULTS: Of 2,169.730 hospitalizations in patients with OSA, 20.1% had comorbid depression. Matched cohorts included 846,150 admissions in both groups: OSA+D+ and OSA+D-. Both cohorts predominantly comprised Caucasians, the elderly (median age, 64 vs. 65 years), and females (55.5% vs. 55.2%). OSA+D+ cohort had a higher prevalence of hypertension, diabetes, hyperlipidemia, congestive heart failure, anemia, smoking, substance abuse, prior myocardial infarction (MI), transient ischemic attack (TIA), TIA/stroke, and venous thromboembolism than the OSA+D- group (all P < 0.001). Paradoxically, there was decreased risk of all-cause mortality [odds ratios (OR): 0.79, 95% confidence interval (CI): 0.73-0.86], major adverse cardiac and cerebrovascular events (OR: 0.83, 95% CI: 0.80-0.87), acute MI (OR: 0.80, 95% CI: 0.76-0.85), dysrhythmia/atrial fibrillation (OR: 0.81, 95% CI: 0.79-0.83), and cardiac arrest including ventricular fibrillation (OR: 0.65, 95% CI: 0.73-0.82) in the OSA+D+ cohort (P < 0.001). CONCLUSION: OSA+D+ patients had better in-hospital outcomes as compared to OSA+D- despite having a higher burden of comorbidities. Additional research is warranted to validate this paradoxical effect of depression in OSA.